Crystal symmetries : Shubnikov Centennial papers - Hargittai, Istvan; Vainshtein, B. K. (Boris Konstantinovich), 1921-; Udalova, V. V.; Rodin, Ervin Y., 1932-; Shubnikov, A. V. (Aleksei Vasilevich) (International series in modern applied mathematics and computer science, 1988)
Crystal Symmetries is a timely account of the progress in the most diverse fields of crystallography. It presents a broad overview of the theory of symmetry and contains state of the art reports of its modern directions and applications to crystal physics and crystal properties. Geometry takes a special place in this treatise. Structural aspects of phase transitions, correlation of structure and properties, polytypism, modulated structures, and other topics are discussed. Applications of important techniques, such as X-ray crystallography, biophysical studies, EPR spectroscopy, crystal optics, and nuclear solid state physics, are represented. Contains 30 research and review papers.